Anxiety in Young People With ADHD: Clinical and Self-Report Outcomes. (January 2015) - Tsang, Tracey W.; Kohn, Michael R.; Efron, Daryl; Clarke, Simon D.; Clark, C. Richard; Lamb, Christopher; Williams, Leanne M.
Objective: (a) To determine the prevalence of comorbid anxiety disorder in ADHD, defined by diagnostic criteria and (b) to compare anxiety as reported by parents and participants with clinician assessment.Method: Children with ADHD were assessed for comorbid anxiety disorder using the Anxiety Disorder Interview Schedule for Children. Parent report (Conners' Parent Rating Scale–Revised: Long version) and self-report (State-Trait Anxiety Inventory and Brain Resource Inventory for Screening Cases–Child version) scales were used to assess anxiety. The ADHD–Rating Scale IV was used to measure ADHD symptoms.Results: Of 134 participants (11.0 ± 2.6 years), 31.3% had comorbid anxiety disorder. Comorbid anxiety disorder was associated with greater severity of ADHD. Anxiety symptoms from parent reports ( p < .05) but not from child/self-report ( p > .05) correlated with clinician assessment.Conclusion: Assessment for comorbid anxiety disorder and inclusion of parent rating in this assessment are important components of ADHD treatment in children and adolescents.